The informativeness of field tests and laboratory assessments in forecasting the Actual Performance of Swimmers - Zuoziene, I. J.; Poderys, J. L. (Biomechanics and Medicine in Swimming XI - Abstracts, 2010)
INTRODUCTION: Various methods can be applied in assessing the level of fitness and functional condition of athletes, as well as in forecasting their performance. Still the specific nature of the kind of sports is a significant factor in selecting tests and control exercises. Therefore the adapted tests, i.e. the tests when the load of movements corresponds to the specific character of the sports movements performed or the testing is carried out just by assessing competitive physical loads, are more suitable for assessing special fitness of athletes in all sports. The aim of the study was to compare the informativeness of field tests (research done in the swimming-pool) and laboratory assessments in forecasting the possible performance of athletes in the 50 m distance. METHODS: The sample was comprised of 12 swimmers (age - 18.63 ± 0.6 years, body mass - 72.6 ± 2.57 kg). First, each participant performed the tests in the water. The special field tests were meant to establish the indices of muscle power and anaerobic capacity, and the subjects performed a control 50 m freestyle swim the best they could. After two days the indices of relative muscle power (W/kg), anaerobic power, anaerobic capacity, anaerobic performance and functional indices of cardiovascular system were taken. RESULTS: The obtained results showed that well-trained swimmers, in comparison with the poor ones, had the highest values in muscle power, anaerobic power, anaerobic capacity and some cardiovascular indices, such as PWC170, more optimal values or relative indices such as velocity of adaptation to loads, ratio JT/RR of ECG. The results in vertical high jump test and relative muscle power showed weak correlation with the 50 m time swim. Relatively small values of correlation were found in the anaerobic power, and higher values - in the anaerobic capacity indices obtained during the laboratory tests. The highest values in correlation between the results in control swim and the assessed indices were obtained during the testing in field conditions. DISCUSSION: These indices are significant and should be used in doing laboratory research in the functional condition and level of fitness among swimmers. The sum total of indices registered with the help of the computerized ECG analysis program enables us to single out the elements restricting the working capacity of athletes as well as to provide individual recommendations about monitoring the training process.